Weightage of Mature Leaf in Eucalyptus Clones in Characterization and Variability Assessment for DUS Testing (Distinct, Uniform and Stable) using MuInvariant Analysis - Anantha Lakshmi, M.; Vinoth Kumar, A.; Chandrasekar, R.; Sivakumar, V.; Nicodemus, A. (Indian Forester, 2020)
The studies were undertaken to develop DUS testing guidelines of selected 25 Eucalyptus clones from commonly available 82 clones from Institute of Forest Genetics and Tree Breeding (IFGTB).Â  The results revealed that all individual clones showed considerable variation in qualitative, pseudo-qualitative and quantitative characteristic traits (17 morpho-metric traits) of Mature leaves and were grouped into different categories. The traits like leaf shape, base shape, apex shape, margin, symmetry, petiole length, lamina area, length, breadth, perimeter, convex perimeter, curve length, curve width, roundness, aspect ratio, convex area and full ratio were identified as grouping traits. The weightage of the quantitative traits were proven by Multi-variant analysis. In Canonical Discriminant analysis, three significant discriminant functions, which had Eigen value >1 and this 3 values accounted for a cumulative variation of 76.2%. In Principal Component Analysis, two significant principal components (PCs) extracted had Eigen value >1 and out of 12 this two values accounted for a cumulative variation of 89.47%. In Eucalyptus clones the dendrogram drawn depicted three distinct clusters based on the similarity using Pearson correlation coefficient method. The dendrogram drawn depicted three distinct clusters based on the euclidean distances grouped them by dissimilarity using agglomerative hierarchical clustering technique (Wardâ€™s method).